What does It Mean to be a Women-Soldier in Contemporary Military Conflict? - Ulozaitė, Milda (Politologija, 2024)
This paper examines the experiences of Ukrainian women-soldiers during Russia’s full-scale invasion in years 2022–2023. War is often perceived as an exclusively male domain, making women’s experiences invisible or irrelevant. This study seeks to incorporate women’s perspectives into the discourse on war and explore their position in the military, as well as the impact of their participation in military conflicts on broader Ukrainian society.The paper analyzes material from thirteen in-depth semi-structured interviews, presented through several meaningful dimensions: the motivations of women joining the Ukrainian Armed Forces, their tasks and roles in the war, the influence of technology on the positions held by women, the identity and transformation of women-soldiers and the perspectives of the interviewees on how others view women in the military, as well as their impact on the army and broader Ukrainian society. These thematic areas are basis an image of the Ukrainian woman soldier during Russia’s large-scale invasion.
Keywords: women-soldier; Ukraine women-soldier; women in military; women and war; women-soldier in Russia‘s full-scale invasion